To determine which expression is not equivalent to \(3x - 2\), let's simplify each option and see if it simplifies to \(3x - 2\).
-
Expression: \(2x + 2 + x\) \[ 2x + 2 + x = (2x + x) + 2 = 3x + 2 \] This simplifies to \(3x + 2\), which is not equivalent to \(3x - 2\).
-
Expression: \(3 - x + 2x - 5 + 2x\) \[ 3 - x + 2x - 5 + 2x = (3 - 5) + (-x + 2x + 2x) = -2 + 3x = 3x - 2 \] This simplifies to \(3x - 2\), which is equivalent.
-
Expression: \(x + x - 1 - 1 + x\) \[ x + x - 1 - 1 + x = (x + x + x) + (-1 - 1) = 3x - 2 \] This simplifies to \(3x - 2\), which is equivalent.
-
Expression: \(4x - 4 - x + 2\) \[ 4x - 4 - x + 2 = (4x - x) + (-4 + 2) = 3x - 2 \] This simplifies to \(3x - 2\), which is equivalent.
Based on the simplifications, the only expression that is not equivalent to \(3x - 2\) is:
\(2x + 2 + x\).